Development Pocket Book Based on Local Culture of Dompu Bima to Improve Speaking Skills of Students MTSn 1 Dompu: Jumratun Aulia*, Arif Bulan, Nur Wahyuni - Jumratun Aulia (Samudra Publisher, 2023)
As a result of the availability of learning pocketbook, understanding and mastery of certain materials must be improved. Therefore, for junior high school students learning that is supported by the right pocketbook is very important because it can facilitate teachers in transferring knowledge and make it easier for students to master the concept of English Pocketbook. Therefore, the researchers developed an Development of A pocketbook based on local culture of Dumpiness to Improve the speaking skill Concept Mastery in the fifth grade English subject at MTsN 1 Dompu. This study purposes to find out the product validity of the pocketbook based on local culture of Dompu to improve the speaking skill, and to find out the effectiveness learning media and find out how the level of feasibility and effectiveness of the media so as to produce valid, effective. This study uses the Research and Development (R&D) ADDIE model, which involves 5 main steps, namely: 1) Analysis, namely analyzing student needs and analyzing curriculum, 2) Development, 3) Product design, 4) Implementation, and 5) Evaluation. The results of this assessment indicate that the English pocket book based on local culture has very good validity according to material experts getting a percentage of 85%, material experts 90%, teacher assessments 90% and student responses 84% which means this Learning Media “Worthy” to use.